Postoperative effect of radiofrequency treatments on the rabbit dermal collagen fibrillary matrix. Issue 3 (28th August 2012) - Kwak, Hyung‐Woo; Choi, Samjin; Cheong, Youjin; Burm, Jin Sik; Jin, Kyung‐Hyun; Park, Hun‐Kuk; Shin, Jae‐Ho
<x xml:space="preserve">Abstract</x> This study quantitatively examined the short and mid‐long term effects of radiofrequency (RF) treatment on the normal dermal collagen fibrils of live rabbits. Effects were evaluated by histology and scanning probe microscopy analysis of dermal tissues treated using three RF energy levels (10, 20, and 30 W) and either a single‐ or multiple‐pass procedure. Progressive changes in the morphology of rabbit dermal collagen fibrils were investigated over a 30‐day post‐treatment period. All RF‐treated groups, except for the low‐energy group (10 W), displayed more prominent inflammatory responses compared to the control. This inflammatory response was more prominent a day after treatment. Dermal tissues 30‐days after RF treatment exhibited prominent myofibroblast activity associated with collagen contractile activity during wound healing in addition to chronic inflammation. A decrease in the morphology of dermal collagen fibrils after RF treatment continued until seven days postoperatively. The collagen fibril diameter increased to near baseline at 30 days postoperatively. Low‐energy and multi‐pass treatments resulted in greater collagen fibril contraction and recovery at the nanostructural level at 30 days postoperatively than did a single high‐energy treatment. Microsc. Res. Tech. 76:219–224, 2013. © 2012 Wiley Periodicals, Inc.